Task Scheduling Algorithms for Multi-Carrying Robots - Ledziński, Damian; Śmigiel, Sandra; Zabłudowski, Łukasz; Zdrojewski, Jarosław (Advances in Manufacturing Engineering II, 2015)
In recent years, problem of task scheduling and allocation of resources has become the subject of many research. The interest of this issue, due to the necessity develop a perfect model, which properly mapped the many of logistical environment. Optimal appoint the path of robots, and also allocate the respective tasks and their order, is the key to solve this problem. For this purpose, was developed the virtual environment, which mapping the activities, taken in this area. Transport these resources is performed in real-time. The task is called by the transport of resources, performed by the robot, between the place of start point to point of distribution. Distribution point is called by the place for downloading and putting the resources by customers. In this article, presents the algorithms relates to aspects of the management of work and planning of task for robots. The results shows the times of the tasks, as well as the times of services the customers, via uses the different algorithms of working robot, and also the amount of consumed the energy, during the performed tasks.